Cyberbullying and Its Impact on Adolescent Emotional Well-Being - M Zainul Hafizi (International Journal of Applied Research and Sustainable Sciences, 2024)
The proliferation of social media networks has been remarkable, offering easy access and the ability to connect with a vast network of friends, which has captivated people of all ages and social backgrounds. This enthusiasm for social media is particularly prominent among teenagers. While social networks provide a platform for emotional expression, unfortunately they are also used to vent anger and use insults and derogatory comments, a phenomenon commonly known as cyberbullying. This section aims to explore the impact of cyberbullying on adolescents within the realm of social media. A literature review method was used, taking articles and journals published between 2013 and 2023, collected from the Google Scholar electronic database. Findings from numerous studies consistently highlight that cyberbullying on social media significantly impacts adolescents, affecting them across psychological, physical, and social dimensions. Importantly, this impact goes beyond just the victim, also affecting the perpetrator and even bystanders.